“I’ve heard of it, yes, but I can’t remember what exactly it was”: a qualitative study on awareness, knowledge, and use of the UV index - Diehl, Katharina; Görig, Tatiana; Jansen, Charlotte Elisabeth; Battenberg, Maike Carola; Pfahlberg, Annette B.; Gefeller, Olaf (International journal of environmental research and public health, 2021)
Pharmacists and pharmaceutical technicians play an important role in counselling customers regarding sunscreen use and sun protection measures. A potentially helpful tool that can be used during counselling is the ultraviolet index (UVI), which informs individuals when and what sun protection measures are needed at a specific place and time. Our aim in this qualitative study was to explore awareness, knowledge, and use of the UVI during counselling in pharmacies. We used semi-structured interviews with pharmacists and pharmaceutical technicians (n = 20) to answer our research questions. Interviews were audiotaped, transcribed verbatim, and analyzed using qualitative content analysis. During the interviews pharmacists and pharmaceutical technicians revealed a lot of uncertainty and lack of knowledge regarding the UVI. Eight professionals were able to give a correct definition of UVI. Amongst others, the UVI was confused with sun protection factor. Overall, the UVI was hardly used during the counselling of customers. The UVI was developed to provide guidance when which type of sun protection is required to avoid detrimental effects of ultraviolet radiation. For effective implementation, both the general population and health professionals (e.g., pharmacists) have to increase their knowledge about the UVI. This would strengthen its use during professional counselling in pharmacies and may help to reduce the incidence of skin cancer over the long term.
Gesehen am 26.04.2021